3D printed compact heat exchangers with mathematically defined core structures. Issue 4 (7th April 2020) - Kim, Jiho; Yoo, Dong-Jin
Abstract: This paper describes a new design method for generating a compact heat exchanger (CHX) computational model consisting of triply periodic minimal surface (TPMS) core structures. These TPMS-based core structures are not easy to design using existing CAD systems, especially in the case of CHXs with complex 3D geometries. In this paper, we introduce a novel CHXs design strategy based on the calculation of volumetric distance fields (VDFs). All geometric components, including TPMS-based core structure, heat exchanger exterior shape, and a set of parts for inlet and outlet, are expressed as VDFs in a given design domain. This VDF-based geometric components description allows for the computationally efficient design of a complex-shaped CHX computational model with high levels of geometric complexity. In conjunction with several TPMS-based CHX prototypes built with additive manufacturing (AM) technologies, we describe and discuss the design and manufacturing results for a wide range of CHXs with various geometries to validate the effectiveness of the newly proposed design method. Besides, by examining the heat transfer performance experimental data, we show that the innovative CHX production method using the combination of VDF-based Boolean operations, TPMS-based core structures, and AM technologies proposed in this paper can create an ultra-efficient CHX while maintaining an allowable pressure drop. Graphical Abstract: